2022
DOI: 10.22469/jkslp.2022.33.3.130
|View full text |Cite
|
Sign up to set email alerts
|

Current Status and Perspectives of Telepractice in Voice and Speech Therapy

Abstract: Voice and speech therapy can be performed in various ways depending on the situation, although it is generally performed in a face-to-face manner. Telepractice refers to the provision of specialized voice and speech therapy by speech-language pathologists for assessment, therapy, and counseling by applying telecommunication technology from a remote location. Recently, due to the pandemic situation and the active use of non-face-to-face platforms, interest in telepractice of voice and speech therapy has increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…Non–face-to-face speech therapy was initially proposed as an alternative method in countries with huge lands, such as the United States and Australia, even before the pandemic. In fact, studies have shown that this method can be effective in treating patients with neuro-lingual disorders, such as dysarthria and apraxia [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Non–face-to-face speech therapy was initially proposed as an alternative method in countries with huge lands, such as the United States and Australia, even before the pandemic. In fact, studies have shown that this method can be effective in treating patients with neuro-lingual disorders, such as dysarthria and apraxia [ 8 ].…”
Section: Introductionmentioning
confidence: 99%